APPLICATION OF BROWN AND LEVINSON’S MODEL ON JOE BIDEN’S VICTORY SPEECH: A CASE ON POLITENESS STRATEGY - Anita Purba; Tutiariani Nasution; Marhaeni KD Matondang; Zulkarnain Zulkarnain; Ridwin Purba (University of Kuningan, 2023)
This research discussed about politeness strategies in Joe Biden’s victory speech. The researcher used theory of Brown and Levinson (1987). This theory to analyzed the types of politeness strategy and the dominant types in Joe Biden victory speech. The source of the data was taken from Joe Biden’s speech in YouTube Its about 15 minutes, 19 seconds. This speech was published at 8 November 2020. The researchers chose Joe Biden’s speech because the researcher found that the types of politeness strategy in this speech. the researcher found 22 data and three types of politeness strategy namely positive politeness 18 (81.8%), negative politeness 1 (4.5%) and off record indirect strategy 3 (13.6%). Positive politeness that found in this speech namely: uses promise, intensifity interest to the hearer, be optimistic, repetition, joke, assume or assert reciprocity, offer, and use rhetorical strategy, negative politeness that found in this speech was use pessimistic and off record indirect strategy namely use metaphors and give hints or directions. The most dominant types in Joe Biden Victory speech was positive politeness strategy. Positive politeness used in the speech so that make good communications between the speaker and the hearer and also make the situations comfortable, relax and make a pleasant situation in doing communication.